Pemahaman Guru Terhadap Peristiwa G 30 S PKI Sebagai Informal Content Mata Pelajaran PPKn - Inka Attahu Ulfa; Adelina Hasyim; Hermi Yanzi (FKIP Unila, 2018)
The purpose of this study is to explain the teachers understanding of events g 30 s PKI as informal content of Pancasila and Civic Education subjects in Madrasah Aliyah Masyariqul Anwar Bandar Lampung. The research method used in this research is qualitative descriptive with the subject of one research of Pancasila and Civic Education teacher, three studens in the tenth grade were taken on the grade level (low, medium, high) and vice principal of the curriculum field. Data collection techniques use guidance test guidelines interviews, observasion guidelines, and documentation guidelines, while data analysis using credibility test with triangulation. The result of this study indicate that the teachers of Pancasila and Civic Education have given responsive and proactive attitude to the film G 30 S PKI as informal material through formal mterials related to the threat to the state and efforts to solve it in the field of ideology, politics, economy, sicial culture and defense and security in Bhinaka Tunggal Ika. the response of lesrners can be see from the understanding od students interpret an event objectively and the school support screening G 30 S PKI given to the students by giving permission and facilities needeed by teachers PPKn.Tujuan Penelitian ini untuk menjelaskan pemahaman guru terhadap peristiwa G 30 S PKI sebagai Informal Content mata pelajaran PPKn di Madrasah Aliyah Masyariqul Anwar Bandar Lampung. Metode penelitian yang digunakan dalam penelitian ini deskriptif kualitatif dengan subjek penelitian satu Guru PPKn, tiga peserta didik kelas X diambil berdasarkan tingkatan nilai (rendah, sedang, tinggi) dan wakil kepala sekolah bidang kurikulum. Teknik pengumpulan data menggunakan pedoman tes, pedoman wawancara, pedoman observasi, dan pedoman dokumentasi, sedangkan analisis data menggunakan uji kredibilitas dengan triangulasi. Hasil penelitian ini menunjukan bahwa guru PPKn telah memberikan sikap responsif dan proaktif pada film G 30 S PKI sebagai materi informal melalui materi formal yang berhubungan dengan ancaman terhadap negara dan upaya terhadap penyelesaiannya dibidang ideologi, politik, ekonomi, sosial budaya serta pertahanan dan keamanan dalam Bhineka Tunggal Ika. Respon peserta didik dapat dilihat dari pemahaman peserta didik memaknai sebuah peristiwa secara objektif serta pihak sekolah mendukung pemutaran film G 30 S PKI diberikan pada peserta didik dengan memberikan izin dan fasilitas yang dibutuhkan oleh guru PPKn.Kata kunci : informal content, pemahaman guru, peristiwa G 30 S PKI.